If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -21 + 5 + -9 = 3(t + -4) + -5 Combine like terms: -21 + 5 = -16 -16 + -9 = 3(t + -4) + -5 Combine like terms: -16 + -9 = -25 -25 = 3(t + -4) + -5 Reorder the terms: -25 = 3(-4 + t) + -5 -25 = (-4 * 3 + t * 3) + -5 -25 = (-12 + 3t) + -5 Reorder the terms: -25 = -12 + -5 + 3t Combine like terms: -12 + -5 = -17 -25 = -17 + 3t Solving -25 = -17 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. -25 + -3t = -17 + 3t + -3t Combine like terms: 3t + -3t = 0 -25 + -3t = -17 + 0 -25 + -3t = -17 Add '25' to each side of the equation. -25 + 25 + -3t = -17 + 25 Combine like terms: -25 + 25 = 0 0 + -3t = -17 + 25 -3t = -17 + 25 Combine like terms: -17 + 25 = 8 -3t = 8 Divide each side by '-3'. t = -2.666666667 Simplifying t = -2.666666667
| 71=6(4n-8)-7n | | 2(x-5)=3(x-1) | | s+6=78 | | 2x+3y-5x+5y= | | 5(1+6a)=-39+8a | | 2+2v=-2 | | 2z^3+9z^2=5z | | 5b-16-8n=-10 | | 7(y+1)=49 | | K=17 | | X+3=-32 | | 15-f=-23 | | 4-5(x+3)=25 | | -22+7r=6(r-4) | | 3x+7+6x+11=90 | | 4x+1=11x | | -2(5y+5)=4 | | 3*x=10 | | 8+16=-3(5x-8) | | 9(6x-5)=279 | | 22x-16x+12=-15+3x+12+6x | | 5x-9=13-x | | 7=20 | | 120*24= | | -30+5n=4+4(1+6n) | | -4(x+8)=-3x-5 | | 4(y+5)=-6(2y-1)+4y | | x^2+8x+8=o | | -5x=5x-100 | | 0.8x+.06(x+9)=1.24 | | 8w-33=-5(w+4) | | 102=-5(3-5m) |